Effects of downstream ramp on the fuel diffusion of single cross jet at supersonic flow: Computational study. (October 2022) - Li, Z.; Abu-Hamdeh, Nidal H.; Bantan, Rashad A.R.; Musa, Awad
Highlights: Effect of downstream ramp on the mixing of cross jet at supersonic flow is studied. The mixing performance of the air/fuel jets in various injector types is investigated. Angle effect of downstream ramp on mixing performance is fully investigated. CFD approach is applied for the simulation of the cross jet with downstream ramp. The fuel mixing of the lobe injector is more efficient than rectangular and circular nozzle. Abstract: In this research, all-inclusive efforts are performed to understand the impact of downstream ramp on fuel distribution of cross jet at high-speed flow inside the combustion chamber. Three different jet injectors have been examined to find the efficient injector (3-lobe, rectangular and circular nozzle) for this configuration. The simulation of the proposed configuration is done by Computational Fluid dynamic via solving RANS equations. SST turbulence model is applied for the computational modeling of the compressible flew inside the combustor. It is also found that the flow recirculation behind the ramp significantly augments vortex feature downstream of fuel jet and this increase the fuel mixing in combustion chamber. The archived outcomes display that rising the angle of the downstream ramp from 10 to 30˚ augments fuel mixing up to 30% inside the combustion chamber. According to our results, the flow circulation downstream of the 3-lobe injector in presence of downstream ramp (30˚) is more than 200% than other nozzle types. Our findings also show that the mixing performance of rectangular jet spanned in the depth of domain is more efficient than other nozzles.